Copper-mediated radioiodination and radiobromination via aryl boronic precursor and its application to 125I/77Br–labeled prostate-specific membrane antigen imaging probes. (1st September 2022) - Kondo, Yuto; Kimura, Hiroyuki; Sasaki, Ichiro; Watanabe, Shigeki; Ohshima, Yasuhiro; Yagi, Yusuke; Hattori, Yasunao; Koda, Manami; Kawashima, Hidekazu; Yasui, Hiroyuki; Ishioka, Noriko S.
Graphical abstract: Abstract: Prostate-specific membrane antigen (PSMA), expressed in prostate cancer cells, is being investigated extensively worldwide as a target for imaging and therapy of prostate cancer. Various radioiodinated PSMA imaging probes have been developed, and their structure has a peptidomimetic urea-based skeleton as a pharmacophore. For direct radioiodination of molecules containing these peptidomimetic structures, prior studies performed radioiododestannylation or electrophilic radioiodination of tyrosine residues. However, although these radiolabeling methods are frequently used, there are some issues with precursor toxicity and by-product production. Therefore, it is required to investigate a radiolabeling method that can be used for the radiosynthesis of radioiodinated PSMA imaging probes with urea-based peptidomimetic structures. We recently reported that copper-mediated radioiodination via a boronic precursor is an effective method for directly labeling a peptide. This radiohalogenation method was expected to be an effective method for radiosynthesis of PSMA imaging probes with a peptidomimetic structure. In this study, to confirm that this labeling method applies to the synthesis of the PSMA imaging probe, we synthesized PSMA imaging probes labeled with 125 I and 77 Br ([ 125 I] m IB-PS and [ 77 Br] m BrB-PS) using a copper-mediated radiohalogenation via common boronic precursors and investigated optimal boronic precursor and labeling conditions. As a result, the radiochemical yields of [ 125 I] m IB-PS and [ 77 Br] m BrB-PS were improved to > 93% at room temperature by optimizing the structure of the boronic precursor. We demonstrate that copper-mediated nucleophilic radiochemistry using a boronic precursor is a promising radiosynthetic method of PSMA imaging probes. Although we focused on the synthesis of PSMA imaging probes, the results in this study will also be useful for the synthesis of various radioiodine or radiobromine-labeled bioactive molecules.